Itikad Baik dalam Perjanjian Jual Beli dengan Metode Pembayaran Cash on Delivery - Tuti Haryanti (Jurnal Ilmiah Penegakan Hukum, 2021)
This article aims to discover the essence of good faith in a sale and purchase agreement using the Cash on Delivery payment method. Cash on Delivery is a payment method that is in demand by many buyers, because payment is made when the goods are received. Problems arise when the seller has good intentions in sending the goods according to the order but the buyer refuses to make payment without reason. This type of research is qualitative with the type of normative research. The legal material is analyzed qualitatively by presenting theory, logical principles, to obtain scientific results that are scientific in nature. The results showed that good faith is a basic principle that must be guided by the parties in formulating an agreement. Good faith in the sale and purchase agreement with the Cash on Delivery system contains a value of honesty, appropriateness, fairness, balance, can build trust, create legal certainty, and provide comfort for the parties. Therefore, the principle of good faith needs to be upheld in online buying and selling transactions and there is a need for provisions that guarantee legal protection for the rejection of goods without reason